(untitled) (Nigerian Journal of Health Sciences, 2023)
Changes in refraction are one of the problems that have been associated with changes in blood glucose level as well as glycemic control. A 52-year-old teacher was seen on account of bilateral poor vision a few days after commencement of treatment for diabetes mellitus. Unaided visual acuity (VA) was count fingers at 3 m in either eye which improved to 6/18 with a pin‑hole. Refraction at presentation was +2.50DS/−0.50DC axis 90° in the right eye improving VA to 6/5 and +3.00DS/−0.50DC axis 90° in the left eye improving VA to 6/9. No other ocular abnormality was detected. Uncorrected VA improved to 6/12 and 6/18 in the right and left eyes respectively after 2 weeks of control of blood sugar. Refraction changed to +1.00DS and +2.00DS −0.50DC axis 140 in the right and left eyes, respectively, improving VA to 6/4 in both eyes. Rapid glycemic control caused temporary severe visual impairment in the patient presented. It is important for the endocrinologist to be aware of this possibility and warn patients to avoid medical mistrust.